Frações contínuas : uma abordagem teórica com aplicações para o ensino médio - OLIVEIRA, Emanoel Rodrigo Tenório de (2016)
This work studies the Continued Fractions, more speci fically the Simple Continued Fractions, as well as some of its applications. Several articles and works were used as a base of this dissertation, which have contributed not only to its development, in a systematic way, but also to its main purpose: to propose some applicationss to be worked with High School students.